Association of Genetic Risk Score With NAFLD in An Ethnically Diverse Cohort. Issue 10 (18th June 2021) - Wang, Jun; Conti, David V.; Bogumil, David; Sheng, Xin; Noureddin, Mazen; Wilkens, Lynne R.; Le Marchand, Loic; Rosen, Hugo R.; Haiman, Christopher A.; Setiawan, Veronica Wendy
Abstract : Most genetic studies of nonalcoholic fatty liver disease (NAFLD) have been conducted in Whites. In this large and ethnically diverse cohort, we assessed the transportability of previously identified genetic variants for NAFLD, built a genetic risk score (GRS), and examined its association with NAFLD risk in multiple ethnic groups. Thirty previously identified genome‐wide association studies (GWAS) variants ( P < 5 × 10 −8 ) and 17 other variants associated with NAFLD were examined in a nested case‐control study of NAFLD (1, 448 cases/8, 444 controls) in this multi‐ethnic cohort study. We then built a GRS using 11 independent single‐nucleotide polymorphisms from these prior studies and examined its association with NAFLD by cirrhosis status across multiple ethnic groups. Of the 30 GWAS SNPs, 20 (67%) were replicated ( P < 0.05) in the pooled multi‐ethnic population. The highest percentage of replication was seen in Latinos (43%), followed by Japanese Americans (37%), Whites (17%), and Native Hawaiians and African Americans (≤10%). Several genetic variants, including those in PNPLA3 (patatin‐like phospholipase domain containing 3), HSD17B13 (hydroxysteroid 17‐beta dehydrogenase 13), TM6SF2 (transmembrane 6 superfamily member 2), GATAD2A (GATA zinc finger domain containing 2A), GCKR (glucokinase regulator), SUGP1 (SURP and G‐patch domain containing 1), MBOAT7 (membrane bound O‐acyltransferase domain containing 7), TRIB1 (tribbles pseudokinase 1), SAMM50 (sorting and assembly machinery component), and ERLIN1 (ER lipid raft associated 1)– CHUK (component of inhibitor of nuclear factor kappa B kinase complex)– CWF19L1 (CWF19 like cell cycle control factor 1) gene cluster, were replicated in at least two ethnic groups. An 11‐SNP weighted GRS was associated with NAFLD risk in the multi‐ethnic population (odds ratio [OR] per SD increase = 1.41; 95% confidence interval [CI] = 1.32‐1.50), as well as in each ethnic group (OR ranged from 1.30 in African Americans to 1.52 in Latinos). The GRS–NAFLD association was stronger for NAFLD with cirrhosis (OR = 1.67; 95% CI = 1.46‐1.92) compared to NAFLD without cirrhosis (OR = 1.37; 95% CI = 1.28‐1.46) ( P heterogeneity = 0.003). Conclusion: In this ethnically diverse cohort, we replicated several key genetic variants for NAFLD and showed the utility of GRS based on the risk alleles for NAFLD risk stratification in multiple ethnic groups. Abstract : In this large and ethnically diverse study, we assessed the transportability of previously identified genetic variants for NAFLD, built a genetic risk score (GRS) with independent SNPs, and examined its association with NAFLD risk in multiple ethnic groups. Several genetic variants were replicated in at least two ethnic groups. A 11‐SNP weighted GRS was associated with NAFLD risk in the multiethnic population with stronger association for NAFLD with cirrhosis. Our study showed the utility of GRS based on the risk alleles for NAFLD risk stratification in multiple ethnic groups.image